Cutaneous myiasis in an elderly debilitated patient. Issue 779 (September 1990) - Roche, S.; Cross, S.; Burgess, I.; Pines, C.; Cayley, A. C.
Abstract : A 77 year old woman, with chronic immobility, developed bed sores which became infested with maggots. This progressed to cutaneous myiasis which is an uncommon complication of this particular phenomenon.